Cell wall inhibitors increase the accumulation of rifampicin in Mycobacterium tuberculosis. Issue 3 (20th March 2019) - McNeil, Matthew B.; Chettiar, Somsundaram; Awasthi, Divya; Parish, Tanya
Abstract : There is a need for new combination regimens for tuberculosis. Identifying synergistic drug combinations can avoid toxic side effects and reduce treatment times. Using a fluorescent rifampicin conjugate, we demonstrated that synergy between cell wall inhibitors and rifampicin was associated with increased accumulation of rifampicin. Increased accumulation was also associated with increased cellular permeability.